2010
DOI: 10.5194/acpd-10-25329-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deposition of dinitrogen pentoxide, N<sub>2</sub>O<sub>5</sub>, to the snowpack at high latitudes

Abstract: Dinitrogen pentoxide, N2O5, is an important nighttime intermediate in oxidation of NOx that is hydrolysed on surfaces. We conducted a field campaign in Fairbanks, Alaska during November, 2009 to measure the flux (and deposition velocity) of N2O5 depositing to snowpack using the aerodynamic gradient method. The deposition velocity of N2O5 under Arctic winter conditions was found to be 0.59 ± 0.47 cm/s, which is the first measurement of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Poor dispersion conditions, such as those observed in Fairbanks, coupled with emissions of automotive-sourced NO lead to near complete removal of O 3 , and thus, little N 2 O 5 is present for much of the winter (Ayers & Simpson, 2006). As urban-polluted air transports away from the city and mixes with ozone-rich air, nocturnal nitrogen oxide chemistry becomes active (Apodaca et al, 2008;Huff et al, 2011) leading to deposition of nitric acid and particulate nitrate. Joyce et al (2014) considered this chemical-meteorological coupling for Fairbanks wintertime conditions through use of a 1-D chemical transport model and found that N 2 O 5 chemistry was suppressed in the urban airshed, which was consistent with the small mass fraction of nitrate in urban Fairbanks particulate matter, but occurred aloft and downwind and was a strong function of available ammonia, affecting the regional fate of the pollution.…”
Section: Air Pollution Chemistry Under Arctic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor dispersion conditions, such as those observed in Fairbanks, coupled with emissions of automotive-sourced NO lead to near complete removal of O 3 , and thus, little N 2 O 5 is present for much of the winter (Ayers & Simpson, 2006). As urban-polluted air transports away from the city and mixes with ozone-rich air, nocturnal nitrogen oxide chemistry becomes active (Apodaca et al, 2008;Huff et al, 2011) leading to deposition of nitric acid and particulate nitrate. Joyce et al (2014) considered this chemical-meteorological coupling for Fairbanks wintertime conditions through use of a 1-D chemical transport model and found that N 2 O 5 chemistry was suppressed in the urban airshed, which was consistent with the small mass fraction of nitrate in urban Fairbanks particulate matter, but occurred aloft and downwind and was a strong function of available ammonia, affecting the regional fate of the pollution.…”
Section: Air Pollution Chemistry Under Arctic Conditionsmentioning
confidence: 99%
“…This chlorine-activation chemistry can happen quite far inland, as demonstrated by (Thornton et al (2010) and presumably happens at Arctic coastal and even inland locations. Heterogeneous reactions can also occur on ice particles and at the snow surface, leading to deposition of N 2 O 5 (Apodaca et al, 2008;Huff et al, 2011). While the chemical reactions underlying nocturnal nitrogen chemistry appear to be relatively well understood, the way in which vertical mixing brings ozone and NO x together exerts strong controls on the rate of nitrogen oxidation and formation of nitric acid.…”
Section: Air Pollution Chemistry Under Arctic Conditionsmentioning
confidence: 99%
“…Changes induced by this cooling process in the ABL (i.e., density discontinuities) promote the vertical divergence of IR fluxes (Fuggle and Oke 1976;Estournel et al 1983) and induce changes in the turbulent flux regime (Estournel and Guédalia 1985). The SBI is important in regulating turbulent flux regimes in ecosystems and surface energy balance (Cohen et al 2007;Huff et al 2010;Chen et al 2011). However, this radiative equilibrium is fragile and therefore it can be disrupted by either the presence of low-level clouds (Wendler and Jayaweera 1972;Jayaweera et al 1975;Stone 1997) or the development of surface winds (Wendler and Nicpon 1975;Hartmann and Wendler 2005), which consequently destroy the stratification.…”
Section: Introductionmentioning
confidence: 99%
“…To date, study of the impact of nocturnal processes on the lifetime of NO x and the production of reactive halogen species in the marine boundary layer has concentrated on gas-phase reactions and heterogeneous and multiphase processes occurring on/within aerosol particles, with little attention paid to reactions occurring at the air−sea interface (6,7). With nearly half of Earth's population living within 200 km of a saltwater coastline, a significant fraction of NO x emissions are found near coastal waters (4,8).…”
mentioning
confidence: 99%